Isolation and characterization of compounds from Calodendrum capense (Rutaceae) and Lydenburgia cassinoides (Celastraceae) for treatment of fungal and bacterial infections in immunocompromised patients - McGaw, Lyndy Joy (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.